Pelatihan pembuatan hand sanitizer sebagai antiseptik berstandar WHO - Oktoviani, Oktoviani; Rizqoh, Debie; Handayani, Dian; Rachmawati, Indah Dwi; Kumala, Wulan Okta (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
The incessant socialization of the government regarding health protocols to a new life order has resulted in most Indonesians becoming introspective in maintaining cleanliness. However, some of the community also experienced panic, so that they acted unnaturally by buying up more goods than they needed, including hand sanitizers. This is one of the reason the price of hand sanitizers has increased. Thatâ€™s why people need to know how to make hand sanitizers so that they are no longer worry about the scarcity of hand sanitizers and can make their own hand sanitizers. The purpose of this activity is to meet the needs of residents for hand sanitizer as an antiseptic with WHO standards. The method used in training in making hand sanitizers in a direct demonstration. Demonstrations are also supported by a PowerPoint and video that is displayed repeatedly with the help of an LCD projector. This was done to repeat the key points of the demonstration sp that a good level of understanding was achieved by the citizens. Then the Citizen representativeswere asked to repeat the demonstration so that the activities of seeingm listening and practicing the knowledgeÂ of making hand sanitizers were completed. Then at the end of the event, an evaluation was carried out using the discussion or question and answer method. The results of the training in making hand sanitizers have helped meet the needs of residents for hand sanitizers, helped residents to be more independent in meeting their needs for hand sanitizers, and increased knowledge and skills of residents regarding making hand sanitizers as WHO standard antiseptics